Student Perceptions of Learning and Engagement in a Flipped Versus Lecture Course. Issue 3 (September 2019) - Garner, Benjamin; Chan, Mark
Current literature suggests that students have equal or higher learning outcomes in a "flipped" classroom compared with a traditional lecture. However, there are few robust analyses of the flipped-class teaching method. This research uses a yearlong, quasiexperimental study across six sections of a business communication course to track student outcomes and perceptions of student engagement and learning. The results indicate that there were no significant differences between flipped and traditional classes across the learning and engagement variables in how students perceived these different conditions. However, the flipped condition produced better outcomes for oral and written assignments.